Upaya Ibn Rusyd Mempertemukan Agama dan Filsafat - A. Khudori Soleh (AL-Fikr, 2011)
This article investigates Ibnu Rushd’s attempt in reconciliation the dichotomy of religion and philosophy, revelation and reason. At least, there are three ways to deal with it: Firstly, providing a different task area for revelation and reason. Revelation is associated with metaphysical issues, and information of life in the hereafter, whereas ratio is related to the physical problems and nowdays life. Secondly, reconciling the methods used to, according to Ibn Rushd, the rational method of burhani (demonstrative) used in the philosophical sciences can also be used to analyze the religious sciences. Likewise, the primary premises can be generated not only by rational analysis but also by the texts of revelation, so that the results of religious analysis are as valid as philosophical rational analysis. Thirdly, integrating the goals of achievement; revelation and reason, religion and philosophy are both invited and want to reach the truth, if religion and philosophy have the same goal that is the truth. The truth one can not be in contradiction with the other truth.